Enveiskjørt samarbeid? En studie av kommunale ledere og legers erfaringer fra samarbeid med helseforetak om kommunale akutte døgnenheter - Skinner, Marianne Sundlisæter (Nordisk tidsskrift for helseforskning, 2015)
The Norwegian Coordination Reform of 2012 transferred responsibilities from the state-run specialist health service to the municipality-run primary healthcare service, simultaneously aiming to improve coordination and cooperation between the two levels. This article investigates how managers and doctors in the municipalities have experienced cooperation with the hospitals on the service level since the reform was implemented. The study focuses on municipal emergency bed units, which are to be introduced in all 428 Norwegian municipalities by 2016. Qualitative interviews with representatives from eight emergency units were conducted in order to identify routines for hospital-municipality cooperation on the service level. The study indicates that there is a majority of cooperation-passive municipality/hospital constellations and a minority of cooperation-active constellations. Furthermore, it is unclear who has the responsibility for initiating and maintaining cooperation. It is argued that both parties have to be active to establish effective cooperation structures on the service level.